Ancestors and corporate performance: Evidence from the Italian Mass Migration - Cheng, Mingying; Florio, Erminia; Manfredonia, Stefano (Journal of Financial Stability, 2025)
We study the relationship between the behavior of a CEO’s ancestors and firm performance. To do so, we collect detailed information on emigrants from Italian municipalities during the Age of Mass Migration (1892–1924) from Ellis Island ships lists. We adopt an epidemiological approach complemented with an instrumental variables strategy and find that Italian firms managed by a CEO who belongs to a family with past emigration experience tend to perform better and to be more productive. In line with an inter-generational transmission of attitudes hypothesis, we show a positive relationship between the emigration experience of a CEO’s ancestors and alternative measures of corporate risk-taking. In addition, we find a positive relationship between having an ancestor who emigrated during the Age of Mass Migration and FDI to the United States. We also provide evidence that these CEOs have better managerial practices.